2021
DOI: 10.4103/tcmj.tcmj_2_20
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of fibroblast growth factor 23 for abdominal aortic calcification in Indonesian hemodialysis patients

Abstract: Objective: Homeostasis of serum phosphorus and calcitriol level is regulated mainly by fibroblast growth factor 23 (FGF23). Studies show that elevated serum FGF23 level was significantly associated with aortic calcification severity, peripheral blood vessels, and a higher score of coronary artery calcification in patients undergoing hemodialysis. We did this cross-sectional study to determine the FGF23 diagnostic value for abdominal aortic calcification in Indonesian hemodialysis patients. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…This table also observed the high value of sensitivity and specificity of the FGF23 with 100% and 100% respectively, with 95% confidence with (p-value≤0.001). [21] reported that the threshold value for FGF23 was 277 pg/mL and that patient serum levels were much higher. The calculated area under the ROC curves was 0.959; the calculated sensitivity and specificity were 94.0 percent and 84.0 percent, respectively (P< 0.001).…”
Section: Resultsmentioning
confidence: 99%
“…This table also observed the high value of sensitivity and specificity of the FGF23 with 100% and 100% respectively, with 95% confidence with (p-value≤0.001). [21] reported that the threshold value for FGF23 was 277 pg/mL and that patient serum levels were much higher. The calculated area under the ROC curves was 0.959; the calculated sensitivity and specificity were 94.0 percent and 84.0 percent, respectively (P< 0.001).…”
Section: Resultsmentioning
confidence: 99%
“…exhibited signi cantly higher serum FGF23 levels compared to those without such calci cation [15] . However, the signi cance of elevated FGF23 in peritoneal dialysis (PD) patients is less understood, with fewer studies, particularly those related to coronary artery calci cation (CAC).…”
Section: Declarationsmentioning
confidence: 94%